Sentiment analysis as a measure of conservation culture in scientific literature - Lennox, Robert J; Veríssimo, Diogo; Twardek, William M; Davis, Colin R; Jarić, Ivan (Conservation biology, 2020)
Culturomics is emerging as an important field within science, as a way to measure attitudes and beliefs and their dynamics across time and space via quantitative analysis of digitized data from literature, news, film, social media, and more. Sentiment analysis is a culturomics tool that, within the last decade, has provided a means to quantify the polarity of attitudes expressed within various media. Conservation science is a crisis discipline; therefore, accurate and effective communication are paramount. We investigated how conservation scientists communicate their findings through scientific journal articles. We analyzed 15,001 abstracts from articles published from 1998 to 2017 in 6 conservation-focused journals selected based on indexing in scientific databases. Articles were categorized by year, focal taxa, and the conservation status of the focal species. We calculated mean sentiment score for each abstract (mean adjusted z score) based on 4 lexicons (Jockers-Rinker, National Research Council, Bing, and AFINN). We found a significant positive annual trend in the sentiment scores of articles. We also observed a significant trend toward increasing negativity along the spectrum of conservation status categories (i.e., from least concern to extinct). There were some clear differences in the sentiments with which research on different taxa was reported, however. For example, abstracts mentioning lobe finned fishes tended to have high sentiment scores, which could be related to the rediscovery of the coelacanth driving a positive narrative. Contrastingly, abstracts mentioning elasmobranchs had low scores, possibly reflecting the negative sentiment score associated with the word shark. Sentiment analysis has applications in science, especially as it pertains to conservation psychology, and we suggest a new science-based lexicon be developed specifically for the field of conservation.
Keywords: Sharks; culturomía; species at risk; ryby; 语言; sociální média; 濒危类群; Attitude; 文化组学; psicología de la conservación; zvířata; 保护心理学; lenguaje; biodiversidad; conservation psychology; language; žraloci; Fishes; zachování přírodních zdrojů; Social Media; extracción de datos de sitios web; Conservation of Natural Resources; culturomics; 生物多样性; taxones amenazados; threatened taxa; postoj; web scraping; Animals; biodiversity; especies en riesgo; 受胁迫物种; 网页抓取